Model Pengembangan Usaha Tahu (Studi Kasus Pada UMKM HNJ Kota Bekasi) - Setiyadi, Indira Sekar; Trimo, Lucyana; Charina, Anne; Renaldi, Eddy (Universitas Galuh, 2024)
HNJ Tofu Factory is one of the processing industry sectors that produces raw white tofu made from soybeans. The appearance of several problems faced, such as improper business strategy management and tends to be monotonous has resulted into inconsistencies in tofu production and sales which are less significant. The purpose of this research is to optimize the development of business potential by providing HNJ Tofu Factory business model strategy so it can create new value to maintain its business. In this study, the author uses the Business Model Canvas approach to map the business model of the HNJ Tofu Factory and evaluates it using SWOT analysis. The method used in this research is a case study method with a qualitative method and data collection techniques are carried out using observation, interviews and documentation. Based on the research results HNJ Tofu Factory must: (1) Maintaining the price, quality and taste of the tofu products sold, (2) Improving the service and relationships provided to regular and potential customers, (3) Increasing the number of variations of tofu products sold, (4) Increasing the value selling by adding brand labels and packaging, (5) Improving operational management in the business, (6) Adding promotional activities via social media, (7) Improving good and stable pricing strategies, (8) Maintaining good relationships with distributors and customers, (9) Increasing the effectiveness and efficiency of business processes, (10) Increasing sales with website and e-commerce services, (11) Establishing cooperative relationships with government.